Using case study for tertiary education in the field of economics - Jarosław Korpysa (Managerial Economics)
The article has a theoretical and empirical character. It analyses ways in which the case study method is used for tertiary education in the field of economics. The problem is verified on the basis of literature and the results of a questionnaire survey addressed to students of economics and related fields of study